Edukasi dan Workshop Pemanfaatan Herbal Untuk Kanker Serviks Pada Ibu-Ibu PKK di Desa Laban, Mojolaban, Sukoharjo - Novena Yety Lindawati; Lusia Murtisiwi; Tesia Aisyah Rahmania (Jurnal Surya Masyarakat, 2020)
Cervical cancer is one of the causes of death in women. According to WHO data (in 2014) more than 93 thousand cases of death of Indonesian women caused by cancer in which 10% is caused by cervical cancer. This underlies the implementation of Community Service of Program Study S1 Pharmacy STIKES NASIONAL with Himpunan Mahasiswa Farmasi STIKES Nasional (HIMFARNAS) to provide “Education and Workshop on The Use of Herbs Medicine for Cervical cancer in Family Empowerment and Walfare (PKK) Laban, Mojobalan, Sukoharjo”. This activity was attended by 65 participants. The participant was very enthusiasm during the activity. This activity is carried out in the form of promotive, preventive, curative, and rehabilitative through education and workchops on the use of herbs for cervical cancer. Evaluation of activities is done by giving a pretest and posttest. The first education was presented by Lusia Murtisiwi who delivered material about its causes, risk factors and symptoms cervical cancer that need to be concern as well as medical treatment. Education about surrounding natural materials that can be used for alternative therapies to accompany cervical cancer treatment presented by Novena Yety Lindawati. The workshop was guided by HIMFARNAS who trained participants in the manufacturing and packaging of “ROMANSA” products. This product consists of anticancer effect which include rosella and sirsat leaves and honey as the sweetener. These beverage products can be consumed by themselves or sold as a home industry business for Family Empowerment and Walfare (PKK). The results of this activity showed an increase in knowledge of the Family Empowerment and Walfare (PKK) participants about preventive measures, early detection of cervival cancer, and supporting therapies for handling cervical cancer naturally, as indicated by an increase in posttest values from average 60.8 to 96.2. In addition, the results of evaluations of overall community service satisfaction programs are very good.